A PRAGMATIC APPROACH TO THE SYSTEM OF SPEECH - Nuritdinova Ra’no Sevdiyevna; Jumayeva Samara Erkin qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article examines the use of linguistic units in conjunction with other non-linguistic means in the speech process, pragmatics as a field of study of the effectiveness of speech communication. Verbal communication is thought to be the interaction of communicators and the effective product of language and the object of study of pragmatics.